2017
DOI: 10.20944/preprints201706.0117.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale, Multi-temporal Remote Sensing of Palaeo-river Networks: A Case Study from Northwest India and its Implications for the Indus Civilisation

Abstract: Abstract:Remote sensing has considerable potential to contribute to the identification and reconstruction of lost hydrological systems and networks. Remote sensing-based reconstructions of palaeo-river networks have commonly employed single or limited time-span imagery, which limits their capacity to identify features in complex and varied landscape contexts. This paper presents a seasonal multi-temporal approach to the detection of palaeo-rivers over large areas based on longterm vegetation dynamics and spect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…There has been debate about the nature of water flow in the Ghaggar-Hakra hydrological system and the dates at which it changed. Remote sensing analysis has highlighted that this system was very complex (e.g., van Dijk et al 2016 ; Orengo and Petrie 2017 , 2018 ), and Optically-Stimulated Luminescence (OSL) dates from northwestern India suggest cessation of major river flow between ∼15–12 kya and ∼8 kya (Singh et al 2017 ). However, other dates suggest parts of the system were active in later periods (e.g., Durcan et al 2017 ; Saini et al 2009 ; Saini and Mujtaba 2010 ; also Clift et al 2012 ; Durcan 2012 ; Giosan et al 2012 ; Maemoku et al 2012 ).…”
Section: Contemporaneity Stability and Instability In Indus Settlemmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been debate about the nature of water flow in the Ghaggar-Hakra hydrological system and the dates at which it changed. Remote sensing analysis has highlighted that this system was very complex (e.g., van Dijk et al 2016 ; Orengo and Petrie 2017 , 2018 ), and Optically-Stimulated Luminescence (OSL) dates from northwestern India suggest cessation of major river flow between ∼15–12 kya and ∼8 kya (Singh et al 2017 ). However, other dates suggest parts of the system were active in later periods (e.g., Durcan et al 2017 ; Saini et al 2009 ; Saini and Mujtaba 2010 ; also Clift et al 2012 ; Durcan 2012 ; Giosan et al 2012 ; Maemoku et al 2012 ).…”
Section: Contemporaneity Stability and Instability In Indus Settlemmentioning
confidence: 99%
“…6). Remote sensing analysis has attested to the existence of a complex network of paleochannels in the area around Rakhigarhi (Orengo and Petrie 2017 , 2018), and preliminary geomorphological analysis has suggested that this area was situated on a braided river system. The nature of this system is currently being assessed through targeted geomorphological research.…”
Section: Contemporaneity Stability and Instability In Indus Settlemmentioning
confidence: 99%
“…In this regard, MSRM cannot be regarded as a complete substitute for multispectral data analysis (as some palaeorivers did not leave any topographic indication of their former course), but as an important complement to these methods. MSRM, however, provides the majority of the data on palaeoriver courses in the study area and has enabled us to complete the ancient palaeoriver network derived from multi‐spectral imagery analysis (Orengo and Petrie, ). More importantly, MSRM has provided essential complementary information, such as the size of the rivers’ channels and the presence and morphology of levees, and it has been able to detect previously unknown bluff lines created by relict large rivers.…”
Section: Application: Micro‐relief Analysis On a Continental Scale Usmentioning
confidence: 99%
“…The algorithm was originally developed to complement large‐area, seasonal, multi‐temporal, multi‐spectral remote sensing approaches that are being applied to the reconstruction of the prehistoric hydrographical network of the Sutlej‐Yamuna interfluve, in northwest India (see later). Our remote sensing‐based method has been able to map more than 8000 km of relict water courses (Orengo and Petrie, ). During the course of that analysis, it became evident that the detection and mapping of topographic features such as levees, relict riverbeds, bluff lines and dune fields could not just increase the number of palaeorivers in our AOI, but also provide significant insights into their nature, behaviour and eventual disappearance.…”
Section: Introductionmentioning
confidence: 99%
“…Further the availability of modern chronological, chemical (including isotope) and high resolution remote sensing data and processing techniques provided a renewed impetus to the study of the "Lost River Saraswati". The palaeodrainage maps associated with Sarswati river were upgraded and refined (Mehdi et al, 2016;Srivastava et al, 2014;Singh et al, 2017;Orengo et al, 2017), chronology of fluvial and aeolian architecture of parts of Saraswati plains developed Saini and Mujtaba, 2010;Clift et al, 2012;Dixit et al, , 2018Singh et al, 2017) and geochemical finger printing of provenance and climate-tectonic correlations worked out (Tripathi et al, 2004;Clift et al, 2012Clift et al, , 2018. The isotopic signatures from buried sediments of the Saraswati like river flowing parallel to the Indus river has been traced from Punjab to Great Rann of Kutch (Gujarat) through Rajasthan (Singh et al, 2016;Khonde et al, 2017).Shallow subsurface studies brought out the buried fluvioaeolian landscape and its relation with the Saraswati River Kshetrimayum and Bajpai, 2012;Sinha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%